2016
DOI: 10.1002/dc.23521
|View full text |Cite
|
Sign up to set email alerts
|

Utility of GATA‐3 in the work‐Up of breast adenocarcinoma and its differential diagnosis in serous effusions:

Abstract: GATA3 is a useful marker in determining the breast origin of metastatic adenocarcinoma in malignant serous effusions. Reactivity to GATA3 may indicate good prognosis. Diagn. Cytopathol. 2016;44:731-736. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…While we believe and have previously shown that micro-arrays constructed from cell blocks are adequate to asses various markers [9,21], the limited number of cells may have resulted in lower marker sensitivity. Overall, however, our results correlate well with previously published data.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…While we believe and have previously shown that micro-arrays constructed from cell blocks are adequate to asses various markers [9,21], the limited number of cells may have resulted in lower marker sensitivity. Overall, however, our results correlate well with previously published data.…”
Section: Discussionmentioning
confidence: 76%
“…It is also expressed in a subset squamous cell carcinomas, salivary gland tumors, mesotheliomas, gynecologic carcinomas and skin adnexal tumors [5,7,8]. In spite of its multi-specific nature, GATA-3 was recently reported to have high positive predicitve value (96.2 %) in determining the breast origin in serous malignant effusion [9]. GATA-3 and estrogen receptor (ER) are involved in a cross-regulatory loop that explains initial reports correlating GATA-3 expression to ER expression; however, recent data support that GATA-3 is expressed in triple negative breast cancer and is more sensitive than the previously described markers gross cystic disease fluid protein 15 (GCDFP-15) and mammaglobin (MAM) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer mainly expresses ER/PR, GATA-3 and Mamma-globin, etc. The positive rate of GATA-3 is 47%-100%, which is a speci c marker of breast cancer 10 . Immunohistochemistry of the breast tumor in this patient showed positive TTF-1, NapsinA, and CK7, supporting the diagnosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer mainly expresses ER/PR, GATA-3 and Mamma-globin, etc. The positive rate of GATA-3 is 47%-100%, which is a speci c marker of breast cancer 7 . Immunohistochemistry of the breast tumor in this patient showed positive TTF-1, NapsinA, and CK7, supporting the diagnosis of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%